Taxonomic account of the ant genus Syscia Roger, 1816 (Hymenoptera, Formicidae) from Asia, with descriptions of two new species from China - Du, Congcong; Xu, Zhenghui; Chen, Zhilin (European Journal of Taxonomy, 2024)
The ant genus Syscia Roger, 1861 is a cryptobiotic group of the subfamily Dorylinae. In this study, eight species of this genus from Asia are recognized, including two new species, Syscia arcodorsa sp. nov. and S. zhoui sp. nov., both described from Guangxi in China. In addition, Cerapachys guizhouensis Zhou, 2006 is redescribed and transferred to Syscia as S. guizhouensis (Zhou, 2006) comb. nov. The species Syscia typhla Roger, 1861 is removed from the ant fauna of China. Lastly, a key to species of Syscia from Asia based on the worker caste is presented.